Revisiting the globular cluster systems of NGC3258 and NGC3268 - Caso, Juan Pablo (2017)
We present a photometric study of NGC3258 and NGC3268 globular cluster systems (GCSs) with a wider spatial coverage than previous works. This allowed us to determine the extension of both GCSs, and obtain new values for their populations. In both galaxies, we found the presence of radial colour gradients in the peak of the blue globular clusters. The characteristics of both GCSs point to a large evolutionary history with a substantial accretion of satellite galaxies.